Listening - Doff, Adrian (Cambridge University Press, 1995)
Listening 1 develops students' ability to understand real-life spoken English through recordings of spontaneous, natural speech, which have been carefully selected and edited for pre-intermediate learners. The activities are designed to encourage students to draw on their own natural listening strategies and to apply them effectively in the context of language learning.